Calcium-Dependent Protein Kinase GhCDPK28 Was Dentified and Involved in Verticillium Wilt Resistance in Cotton - Wu, Yajie; Zhang, Lei; Zhou, Jinglong; Zhang, Xiaojian; Feng, Zili; Wei, Feng; Zhao, Lihong; Zhang, Yalin; Feng, Hongjie; Zhu, Heqin (Frontiers in Plant Science, 2021)
Verticillium dahliae is a soil-borne fungus that causes vascular wilt through the roots of plants. Verticillium wilt caused by V. dahliae is one of the main diseases in cotton producing areas of the world, resulting in huge economic losses. Breeding resistant varieties is the most economical and effective method to control Verticillium wilt. Calcium-dependent protein kinases (CDPKs) play a pivotal role in plant innate immunity, including regulation of oxidative burst, gene expression as well as hormone signal transduction. However, the function of cotton CDPKs in response to V. dahliae stress remains unexplored. In this study, 96, 44 and 57 CDPKs were identified from Gossypium hirsutum, Gossypium raimondii and Gossypium arboretum, respectively. Phylogenetic analysis showed that these CDPKs could be divided into four branches. All GhCDPKs of the same clade are generally similar in gene structure and conserved domain arrangement. Cis-acting elements related to hormones, stress response, cell cycle and development were predicted in the promoter region. The expression of GhCDPKs could be regulated by various stresses. Gh_D11G188500.1 and Gh_A11G186100.1 was up-regulated under Vd0738 and Vd991 stress. Further phosphoproteomics analysis showed that Gh_A11G186100.1 (named as GhCDPK28-6) was phosphorylated under the stress of V. dahliae. Knockdown of GhCDPK28-6 expression, the content of reactive oxygen species was increased, a series of defense responses were enhanced, and the sensitivity of cotton to V. dahliae was reduced. Moreover, overexpression of GhCDPK28-6 in Arabidopsis thaliana weakened the resistance of plants to this pathogen. Subcellular localization revealed that GhCDPK28-6 was localized in the cell membrane. We also found that GhPBL9 and GhRPL12C may interact with GhCDPK28-6. These results indicate that GhCDPK28-6 is a potential molecular target for improving resistance to Verticillium wilt in cotton. This lays a foundation for breeding disease-resistant varieties.